Genetic Diversity in Finger Millet Landraces revealed by RAPD and SSR Markers - Joshi, Bal Krishna; Joshi, Darbin; Ghimire, Surya Kanta (Nepal Journal of Biotechnology, 2020)
Genetic diversity assessment is the preliminary work for development of variety and conservation of diversity. Finger millet is a very important crop in Nepal however, its genetic potential has not been fully utilized. Genetic diversity was assessed in forty landraces of finger millet using 9 RAPD and 5 SSR markers. These landraces were collected from Kaski and Dhading districts. None of single primers of these RAPD and SSR could separate all 40 landraces. The average number of bands were 6.33 and 7.8 per RAPD and SSR primers respectively. Mean polymorphism information content was of 0.314 for RAPD and 0.37 for SSR. Primer OPA-4 produced the highest number of bands and the lowest numbers of bands were produced by OPA-16. Among the SSR primers, SSR-06 produced the highest number of polymorphic bands and UGEP-53 produced the lowest bands. RAPD based dendrogram has generated four clusters and SSR based dendrogram has generated two clusters. In both dendrogram and principal component analyses, Purbeli landrace was found unique locating separately in the cluster and scatter plot. Nei's genetic distance produced by RAPD and SSR primers was similar that is 0.327 by RAPD and 0.296 by SSR markers. Genetic distance produced by SSR markers was higher than distance produced by RAPD marker. These landraces were from two districts and therefore have shown intermediate diversity. These molecular marker-based findings should would be more useful if we could link with agromorphological traits. Inclusion of large number of landraces collected from different areas are required to get higher level diversity in addition to associate genetic diversity with geographical sites. Groupings of these landraces could be useful for selecting landraces in breeding program as well as planning conservation program.